CONCENTRATION OF SODIUM METABISULFITE AND THE DURATION OF BLANCHING THEIR EFFECT ON THE QUALITY OF RED CHILLIES (CAPSICUM ANNUM L.) DRYING USING A SOLAR DRYER DOME - Rahman, Fatur
The drying process plays an essential role in maintaining the quality and extending the shelf life of chili. The longer the drying time will produce dry red chilies that are dark red—the blanching process before drying plays a role in preventing enzymatic and non-enzymatic browning reactions. The use of sodium metabisulfite also plays a role in interacting with the carbonyl group, which can bind melanoidin and prevent the appearance of brown color. Therefore, this treatment is needed to improve the quality and color of red chili after the drying process. This study aims to determine the interaction between sodium metabisulfite concentration and blanching time on the quality of dried red chilies that are dried using a solar dryer dome. This study was conducted using a factorial Completely Randomized Design (CRD) with three levels of treatment with sodium metabisulfite concentration (0.1000 and 2000 ppm) and three levels of treatment duration of blanching (3.5 and 7 minutes), carried out three times so that 27 treatment level. The data were analyzed using Analysis of Variance for normally distributed data, and the Kruskal-Wallis method was used for data that were not normally distributed. Curly red chili that had been blanched with sodium metabisulfite was then dried for seven days in a solar dryer dome. Parameters observed included water content, weight loss, vitamin C, color changes, and hedonic and hedonic qualities. This study showed an interaction between the administration of sodium metabisulfite and the duration of blanching on the vitamin C content of curly red chili from the 0th day of drying to the third day. Administration of sodium metabisulfite accelerated the decrease in water content by an average of 10.91% after drying. However, administration of sodium metabisulfite and duration of blanching did not affect the color change. The administration of sodium metabisulfite with a concentration of 2000 ppm with a blanching duration of 7 minutes has a preference value of 3.3 based on consumer preferences for dry curly red chilies.